Constraints Faced by The Students in Making Virtual Based Tour Videos In Teaching English For Guiding - Made Aryawan Adijaya (Jurnal Pedagogi dan Pembelajaran, 2023)
The low participation of students in learning English for Guiding Class is due to the need for more use of learning media that attracts students to follow the lesson well. The purpose of this study was to find out the obstacles faced by students in implementing virtual-based video tours in the English for Guiding Class. This research is descriptive. This type of research is descriptive qualitative. The methods used in collecting data are observation and interviews. The instrument used in collecting data is a questionnaire. The data analysis technique used is descriptive qualitative analysis. The results of this study indicate that implementing virtual-based video tours causes eight main obstacles that students often face: ICT literacy, finance, internet connection, technical, administration, English proficiency, content knowledge, and time constraints. It was concluded that video tours require special support, such as a solid internet connection and ICT literacy. Further research will likely provide different solutions so that the problems faced by students can be overcome without neglecting the essence of creativity and innovation from video-based virtual tours in English for Guiding Class.